Fulminante Destruktion des Handgelenks nach Teilversteifung durch Tuberkulose = Massive Destruction of the Carpus after Partial Arthrodesis Caused by Tuberculosis - Spies, Christian; Müller, Lars Peter; Unglaub, Frank (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2016)
We present the case of a 75-year-old woman who suffered from a severe carpal collapse caused by tuberculosis after partial wrist arthrodesis.
Gesehen am 13.12.2019
Online-Publikation: 21.5.2015